COPING WITH FLOOD AND DROUGHT: THE GAPS BETWEEN LOCAL RESPONSES AND GOVERNMENT POLICY IN KARANGBINANGUN DISTRICT, LAMONGAN REGENCY, EAST JAVA, INDONESIA - , Ratna Kumala Dewi, Ir. Leksono Probo Subanu, MURP, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
There is a place in Lamongan Regency, which was a stretch of swamp, called Bengawan Jero. This place was originally had function as water catchment area in the past. After The Independence Day of Indonesia, the government tried to utilize this area become fisheries development area because its content a lot of water. The development activities attracted people to come and live there. They do both fish and rice farming in different season. But on the other hand, the people who built their settlement near the riverbank, are vulnerable and affected by the flood every year. This study is about the gap between the government policy and local people who are affected by the flood. This study was located in Waruk village as one of the village which most affected by the flood and located in Bengawan Jero area. Bengawan Jero has a lot of potential resources as fisheries development area. The people take many advantages and can make better income for their live. But the people have to face annual flood which is happened every year. From the government point of view, annual flood is the main problem in this area. However, the local people have their own adjustment action to cope with flood in order to survive. Nowadays, the people also have to face drought problem and getting severe every year. They have to buy water during dry season to irrigate their field and sometimes they also have to buy water for their daily consumption because the water in the river already dried up. The study aims to analyze the attitudes and behaviors of people who are living near the riverbank and get affected by the flood and drought